The Goths in Orosius’ ‘History against the pagans’: between rhetoric and horizon of expectation - Antiqueira, Moisés; Galante, Márcio Augusto (Romanitas - Revista de Estudos Grecolatinos, 2023)
In the final section of his Histories against the Pagans, Orosius gave prominence to the actions and events concerning the presence of the Goths in the Western provinces of the Roman Empire in the early 5th century. Special emphasis is given to some passages in his text (notably those between chapters 37 and 43) concerning two main aspects: on the one hand, the way Orosius sought to set his authority as a scriptor historicus and, on the other, the construction of a temporal dialectic through which the Goths stood as agents of Divine Providence to ensure the maintenance of the Roman Empire in the years to come.